PENGEMBANGAN SOAL LITERASI MATEMATIKA BERBASIS BUDAYA ETNIK MADURA UNTUK SISWA SMP/MTs - Saukiyah, Sitti; Sunardi, Sunardi; Trapsilasiwi, Dinawati (Kadikma, 2017)
Abstract. This research describes the process and the development result development of math literacy based on Madura ethnic culture for SMP / MTs students. This research is a development research that refers to the steps of Plomp model development. In this research, it was produced 1 package of test item consisting of 5 theme questions amounted to 8 questions. The package of test item developed is related to the use of mathematics in social life, especially in Maduran ethnic culture. Before this package of test item was tested, firstly, an assessment by 2 validators is done. On the assessment result of these experts, it was obtained the coefficient of validity of 2.61 with a high validity interpretation. In addition to the packages of test item validated by the validator, the package of test item is also given to 6 students of 8th grade students of MTs Nurul Islam Jember to conduct legibility test. The next stage was testing the package of test in the field. The result of this try out from field was analyzed. The analysis conducted is the validity test for each test item, reliability test, test item differentiation power assessment, test item difficulty level assessment and the level of students' mathematical literacy ability. The results of validity test item on the package of math literacy test item based on Madura ethnic culture obtained all the questions developed were valid. In the package of math literacy test item based on Madura ethnic culture showed high reliability with a coefficient of 0.76. The result of differentiation power test obtained two test items with a category of good, two questions with a category of enough and four problems with a category of bad. On the assessment of difficulty level, it was obtained five questions with a category of difficult, two problems with a category of medium and one problem with a category of easy. The students' math literacy ability level indicated that students were at level 1, level 2, and level 3. Based on the result of the analysis conducted, it can be concluded that the quality of the developed problem package is good. Key Words: Mathematical literacy test items, Madura ethnic culture